La teoría humanista de la administración y su repercusión en la gestión empresarial de las secretarias - Peña Vera, Lesly Annabeth (2021)
The present investigation lays its foundations on the approaches of the Sociologist Elton Mayo who developed for the first time an administrative theory oriented to human relations and the well-being of the worker, the Humanist Theory of administration, and the importance that resides on it in development of the business management processes of the secretaries. This project was carried out in the administrative department of the Hcda branch. Jujanillo de la Compañía agricultural Luderson S.A. Their contributions and approaches lay the foundations of the current administration, however, with the new demands imposed by modern business administration, the fulfillment of tasks is established as a primary objective and the importance of human capital is relegated. The outstanding aspects of the theory such as; work motivation, organizational environment, work well-being and internal communication are placed on a secondary plane. Business management, a science that is also in constant innovation, faces changes in administration to maintain a bearable system that meets all the new standards of modern administration. As a result of this we have the human resource that is under extreme pressure and is returned in a certain way to the old administrative bases.